Welcoming the stranger: religion and attitudes toward social justice for immigrants in the U.S - Davidson, Theresa C. (The journal of religion & society, 2014)
Every major religious tradition contains edicts for social justice on behalf of the marginalized, or, the stranger. However, the influence of religion on attitudes toward immigrants has been understudied. Along with other factors, this project analyzes the influence of religion on public sentiment regarding immigration policy in the United States. We find some effects of religious identification and religious behavior on attitudes toward the right to remain in this country, access to social services, and entitlement to public education. Religious measures show no influence on attitudes toward citizenship rights for children of immigrants born in the United States. Religious individuals and communities may play an important role in the acceptance and integration of immigrants.